A new multichannel method quantitating TUNEL in detached photoreceptor nuclei. (November 2018) - Heisler-Taylor, Tyler; Kim, Bongsu; Reese, Alana Y.; Hamadmad, Sumaya; Kusibati, Rania; Fischer, Andy J.; Cebulla, Colleen M.
Abstract: Nuclear co-localization labels are critical to ocular research. Among these, the TUNEL assay has been established as a gold standard of cell death and apoptosis. While several validated computer-based methods exist to quantitate these markers, including ImageJ Retina Analysis (RA) Toolkit and ImagePro, none verify the count with the nuclear counter stain to confirm nuclear co-localization. We established a new ImageJ-based automated multichannel thresholding (MCT) method to quantitate nuclear co-localized labeling. The MCT method was validated by comparing it with the two published TUNEL analysis in TUNEL-positive photoreceptors in an experimental retinal detachment (RD) model. RDs were induced in murine eyes and cross-sectional images of TUNEL and DAPI counter stain were obtained. Images were classified as "typical" or high density "hotspot" TUNEL regions (n = 10/group). Images were analyzed and compared between the MCT method and the published techniques including both "standard" and "high" settings of the RA Toolkit for detecting lower or higher TUNEL densities, respectively. Additional testing of the MCT method with built-in ImageJ thresholding algorithms was performed to produce fully automated measurements. All images were compared with Bland-Altman mean difference plots to assess the difference in counts and linear regression plots to assess correlation. Comparison between the MCT method and the ImagePro method were found to be well correlated (typical: R 2  = 0.8972, hotspot: R 2  = 0.9000) with minor to non-significant differences. The RA Toolkit settings were found to be mostly well correlated as well (standard/typical: R 2  = 0.8036, standard/hotspot: R 2  = 0.4309, high/typical: R 2  = 0.7895, high/hotspot: R 2  = 0.8738) but were often found to have significantly higher counts than the MCT. In conclusion, the MCT method compared favorably with validated computer-based methods of nuclear marker immunofluorescence quantitation and avoids staining artifacts through the incorporation of the nuclear counter stain to confirm positive cells. Highlights: Current cell death analysis methods do not verify cells with nuclear counterstain. This can lead to artificial or false-positive results. Multichannel thresholding allows counting of nuclear verified cells. Compared favorably to multiple verified and published methods. Automated thresholding algorithms allows rapid and efficient batch analysis.